2022
DOI: 10.3390/ma15072600
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Tribological Behaviour of Nanolubricants during Micro Rolling of Copper Foils

Abstract: Water-based lubricants with different fractions of TiO2 nanoparticles ranging from 1.0 to 9.0 wt% were utilized to study the lubrication mechanisms during micro rolling tests and the tribological behaviour of nanolubricants during the micro rolling of copper foils. The results indicate that the application of TiO2 nanolubricants remarkably improves the surface quality of rolled copper foils during rolling processes. For lubricants with inadequate TiO2 nanoparticles, it is found that few TiO2 nanoparticles ente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 34 publications
(34 reference statements)
0
15
0
Order By: Relevance
“…With the concentration of TiO 2 nanoparticles increases from 1% to 3%, the rolling force decreases from 2.75 to 2.63 kN, which can be attributed to the reduced energy consumption caused by friction during rolling processes. 22 Nevertheless, the rolling force increases from 2.63 to 3.96 kN with the concentration of TiO 2 nanoparticles further increases from 3% to 9%, and this phenomenon can be explained by the aggregation of TiO 2 nanoparticles. 28 During rolling processes, excessive TiO 2 nanoparticles tend to aggregate at contact regions and leads to an increase in COF, thereby causing more energy consumption and higher rolling force.…”
Section: Lubrication Effects Of Water-based Lubricantsmentioning
confidence: 93%
See 2 more Smart Citations
“…With the concentration of TiO 2 nanoparticles increases from 1% to 3%, the rolling force decreases from 2.75 to 2.63 kN, which can be attributed to the reduced energy consumption caused by friction during rolling processes. 22 Nevertheless, the rolling force increases from 2.63 to 3.96 kN with the concentration of TiO 2 nanoparticles further increases from 3% to 9%, and this phenomenon can be explained by the aggregation of TiO 2 nanoparticles. 28 During rolling processes, excessive TiO 2 nanoparticles tend to aggregate at contact regions and leads to an increase in COF, thereby causing more energy consumption and higher rolling force.…”
Section: Lubrication Effects Of Water-based Lubricantsmentioning
confidence: 93%
“…[19][20][21] It is known that inadequate TiO 2 nanoparticles leads to insufficient lubrication during rolling processes, whilst excessive TiO 2 nanoparticles induces marked aggregation at the contact regions, deteriorating the surface quality of the rolled foils. 22 Thus, the study on the concentration of nanoparticles in lubricants is critical to improve the lubrication conditions during rolling processes. Wu et al 23 analysed the effect of water-based nanolubricant containing nano-TiO 2 on friction and wear behaviour of chrome steel at ambient and elevated temperatures, and found that the use of nanolubricant containing an optimal concentration (4.0 wt%) of TiO 2 nanoparticles led to the lowest COF.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To this end, Wu et al [ 37 , 38 ] conducted the hot rolling tests under pure water and water-based TiO 2 nanolubrication conditions, which revealed that the mending and ball-bearing effects of TiO 2 NPs are the primary causes of reduced friction in the contact zone. Moreover, Ma et al [ 39 ] investigated different fractions of TiO 2 NPs in the micro rolling and found that a low fraction of TiO 2 NPs could cause insufficient lubrication. Conversely, excessive TiO 2 NPs could lead to apparent agglomeration at the contact regions, ultimately deteriorating the surface quality [ 34 , 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…Conventional EP and AW additives act by adsorbing active groups to the friction surface or react chemically with the metal surface to form a modified boundary layer. On the other hand, EP and AW nanoadditives can protect frictional mating surfaces mainly through: mending effect, polishing effect, protective film formation mechanism and rolling bearing effect [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%